Pengembangan Kemampuan Literasi dan Numerik Siswa Sekolah Dasar - Muh. Khaedar; Muslimin; Nur Fahmi Indriani (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Teaching Campus Program Class 5 of 2023 is one form of implementation of Merdeka Belajar Kampus Merdeka (MBKM) in the form of teaching assistants to empower students in helping the learning process in elementary schools, one of which is SD Inpres Mangngarabbe which is located at Jl. Bonto Rita, Bisappu District, Bantaeng Regency. The purpose of the Class 5 Teaching Campus Program in 2023 is to assist the school in the teaching process, technology adaptation, and administrative assistance. This program is expected to foster empathy and social sensitivity to existing problems; hone thinking and cooperation skills between teachers and students of the Teaching Campus; develop students' insights, character, and soft skills; Increase the role and real contribution of universities and students in national development. The impact felt by students during the presence of Teaching Campus students accompanying teachers to teach in class is an increase in the percentage of motivation and interest in learning around 80-90%. Teachers and students of the Teaching Campus are required to be able to design learning activities from planning to evaluation in a simpler, creative, and effective way. Teaching Campus students and teachers at school also work together to complete, tidy up and complete the principal's administration. This aims to make it easier for schools when it comes to improve school accreditation